Natural Disasters as Criminogenic Forces A Socio-Legal Analysis with Reference to Pakistan - Zeeshan Shah; Kokab Saeed; Mrs Nadia Noreen; Dr. Sara Qayum; Maryam Sharafat; Sidra Ilyas Advocate (`, 2026)
The 2005 Kashmir Earthquake, whose epicentre was Muzaffarabad, caused more than 73,000 to 87,350 but some estimates were higher than 100,000 casualties, and massive displacement in Khyber Pakhtunkhwa and Kashmir. Although the physical damage that occurred during the disaster was immediate, its socio-legal impacts in the long run have not been well-researched. This paper discusses how far natural disasters can lead to criminogenic forces, which lead to the development of criminal behaviour. This paper examines how structural failures, such as poor rehabilitation and social dislocation, may create entry points to criminality through a socio-legal analysis of a case study of a person who lost his parents in the earthquake and then found himself in a severe state of deprivation in the aftermath of the disaster. The paper also evaluates the possibility of such states resulting in abuse of basic rights and greater susceptibility to state abuses. This paper argues that when natural disasters, together with poor state response, may provide conditions that allow crime to thrive, a re-evaluation of disaster management policies in the light of criminology and human rights is required. Keywords: Criminogenic Forces, Socio-Legal Analysis, epicenter, casualties, deprivation